2021
DOI: 10.3390/pathogens10121632
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal Effect of Snake Venoms and Their Fractions: A Systematic Review

Abstract: Background: Protozoal infection is a lingering public health issue of great concern, despite efforts to produce drugs and vaccines against it. Recent breakthrough research has discovered alternative antiprotozoal agents encompassing the use of snake venoms and their components to cure these infections. This study collated the existing literature to examine the antiprotozoal effect of snake venoms and their fractions. Methods: We conducted a systematic review following the PRISMA guidelines. The PubMed and Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 99 publications
(133 reference statements)
0
12
0
Order By: Relevance
“…Overall, our systematic search identified 24 articles on the bactericidal effect of svPLA 2 s. The majority of the studies (80%) found through the search were on the PLA 2 s of snakes from the Viperidae family, whereas 20% were on the PLA 2 s from snakes of the Elapidae family. There are considerable variations in the composition of snake venoms recorded even from closely related species and within species [6]. Evidence of intra-genus or intra-specific variation in venom compositions has been documented in pit vipers and adders [36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, our systematic search identified 24 articles on the bactericidal effect of svPLA 2 s. The majority of the studies (80%) found through the search were on the PLA 2 s of snakes from the Viperidae family, whereas 20% were on the PLA 2 s from snakes of the Elapidae family. There are considerable variations in the composition of snake venoms recorded even from closely related species and within species [6]. Evidence of intra-genus or intra-specific variation in venom compositions has been documented in pit vipers and adders [36].…”
Section: Discussionmentioning
confidence: 99%
“…Snake venom PLA 2 s (svPLA 2 s) are enzymatic proteins with low molecular weights. They catalyze the hydrolysis of the 3-sn-phosphoglyceride-dependent calcium 2-acyl ester bond, yielding lysophospholipids and fatty acid products [6]. Snake venom PLA 2 s have similar toxicological profiles, including cytotoxicity, myotoxicity, oedema, inflammation, neurotoxicity, hypotension, anticoagulant activity, hemolysis, hyperalgesia, and microbicidal activity [5].…”
Section: Bactericidal Effects Of Snake Venom Pla 2 Smentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are effects of snake venoms on microorganisms. Thus, the venoms can exhibit antiviral (reviewed in [ 6 ]), antibacterial (reviewed in [ 7 ]), and antiprotozoal activities (reviewed in [ 3 , 8 ]). By the present time, snake venom peptides and proteins with such activities have been identified.…”
Section: Introductionmentioning
confidence: 99%